Insights into the historical construction of species-rich biomes from dated plant phylogenies, neutral ecological theory and phylogenetic community structure (2006)
Analytical methods are now available that can date all nodes in a molecular phylogenetic tree with one calibration, and which correct for variable rates of DNA substitution in different lineages. Although these techniques are approximate, they offer a new tool to investigate the historical construction of species?rich biomes. Dated phylogenies of globally distributed plant families often indicate that dispersal, even across oceans, rather than plate tectonics, has generated their wide distributions. By contrast, there are indications that animal lineages have undergone less long distance dispersal. Dating the origin of biome?specific plant groups offers a means of estimating the age of the biomes they characterize. However, rather than a simple emphasis on biome age, we stress the importance of studies that seek to unravel the processes that have led to the accumulation of large numbers of species in some biomes. The synthesis of biological inventory, systematics and evolutionary biology offered by the frameworks of neutral ecological theory and phylogenetic community structure offers a promising route for future work.